Amiloidosis con compromiso cardíaco, hepático e intestinal: caso clínico - Delgado D., Javier; Fuentes G., Rocío; Fuentes V., Marcelo; Iracheta M., Alexis (Revista Hospital Clínico Universidad de Chile, 2025)
Amyloidosis is a rare disease characterized by amyloid deposits in tissues, mainly affecting the kidneys and heart. Diagnosis requires positive evidence of amyloid deposits by Congo red staining. It is usually a disease with a poor prognosis due to late diagnosis and advanced involvement in affected organs. This report presents the case of a 62-year-old woman with a history of recently diagnosed chronic liver damage, which was notable in the liver profile for elevated alkaline phosphatase, hepatomegaly without splenomegaly, and an unknown etiological study. She was admitted in the context of septic shock with an abdominal focus and a history of chronic diarrhea and symptoms of heart failure. During hospitalization, a broad study was carried out with an echocardiographic study suggesting infiltrative disease and biopsies of subcutaneous fat and colon biopsies consistent with amyloidosis. Given the resolution of the septic condition and clinical stability, she was discharged from the hospital with an indication for multidisciplinary outpatient follow-up.